Hormonal Oscillations During the Estrous Cycle Influence the Morphophysiology of the Gerbil (Meriones unguiculatus) Female Prostate (Skene Paraurethral Glands) - Fochi, Ricardo A.; Perez, Ana P. S.; Bianchi, Carlos V. [UNESP]; Rochel, Sabrina S.; Goes, Rejane M. [UNESP]; Vilamaior, Patricia S. L.; Taboga, Sebastiao R. [UNESP]; Santos, Fernanda C. A. [UNESP] (Soc Study Reproduction, 2008)
The hormonal oscillations that occur during the female reproductive cycle influence the morphophysiology of several organs of the reproductive system. The female prostate is a functional organ sensitive to the action of steroidal hormones, but it is not known whether the hormonal oscillations that occur during the reproductive cycle can alter the biology of this gland. Thus, the present work aims to evaluate the morphofunctional aspects of the female prostate during the gerbil estrous cycle. For this purpose, morphological, morphometric-stereological, serological, and immunocytochemical analyses were carried out. The results of the present study show that the hormonal oscillations that occurred during the estrous cycle altered both the structure and functionality of the gerbil female prostate. These alterations include increased prostatic growth and augmented secretory activity during the proestrus and estrus phases and a gradual decrease of the secretory activity and glandular development in the diestrus I and II phases. These cyclical oscillations appear to be determined by the hormonal peaks of estrogen in diestrus II and by the high levels of progesterone during estrus, since the androgen levels remained constant throughout the estrous cycle.
Keywords: estrous cycle; Female prostate; Morphology; Progesterone; Prostate; Steroid hormone